2004
DOI: 10.1177/00238309040470040101
|View full text |Cite
|
Sign up to set email alerts
|

Language-Specificity in the Perception of Paralinguistic Intonational Meaning

Abstract: This study examines the perception of paralinguistic intonational meanings deriving from Ohala's Frequency Code (Experiment 1) and Gussenhoven's Effort Code (Experiment 2) in British English and Dutch. Native speakers of British English and Dutch listened to a number of stimuli in their native language and judged each stimulus on four semantic scales deriving from these two codes: SELF-CONFIDENT versus NOT SELF-CONFIDENT, FRIENDLY versus NOT FRIENDLY (Frequency Code); SURPRISED versus NOT SURPRISED, and EMPHAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 30 publications
2
100
2
Order By: Relevance
“…Generally, friendliness or social interest are two closely related attitudes that seem to be marked by a phrase-final high or rise. These results are generally consistent with results for friendliness obtained for English and Dutch by Chen et al (2001) where higher F0 range and a final rising contour elicited more responses for friendliness.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, friendliness or social interest are two closely related attitudes that seem to be marked by a phrase-final high or rise. These results are generally consistent with results for friendliness obtained for English and Dutch by Chen et al (2001) where higher F0 range and a final rising contour elicited more responses for friendliness.…”
Section: Discussionsupporting
confidence: 91%
“…Cruz-Ferreira (1989), for instance, asked Portuguese learners of English and English learners of Portuguese to indicate meaning differences in intonational minimal pairs (e.g., She gave her dog biscuits*in which either the dog or the person gets biscuits) and reported three strategies: transfer of L1, usage of universal codes (e.g., high pitch for nonfinality, see also Chen, Gussenhoven, & Rietveld, 2004), and choice of the more neutral meaning. Niioka et al (2005) (Dahan, Tanenhaus, & Chambers, 2002;Ito & Speer, 2008;Weber, Braun, & Crocker, 2006).…”
Section: Interpreting Intonational Meaning In L2 225mentioning
confidence: 99%
“…It was first identified in Brown and Levinson (1987) as a possible way to increase perceived politeness and has subsequently been followed up in the literature. For example, an increase in peak height can lead to higher levels of perceived friendliness in Dutch and English (Chen et al 2004); yet Nadeu and Prieto (2011) showed that in Catalan an increase in the final pitch height of yes-no questions led to more impoliteness ratings unless sentences were accompanied by a smiling face. Politeness can also be achieved through accommodation to the interlocutor's pitch range (Lin et al 2006) and speech rate (Ofuka et al 2000).…”
Section: Introductionmentioning
confidence: 99%